1996
DOI: 10.1093/nar/24.3.411
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced activity of an antisense oligonucleotide targeting murine protein kinase C-alpha by the incorporation of 2'-O-propyl modifications

Abstract: We have previously described the characterization of a 20mer phosphorothioate oligodeoxynucleotide (ISIS 4189) which inhibits murine protein kinase C-alpha (PKC-alpha) gene expression, both in vitro and in vivo. In an effort to increase the antisense activity of this oligonucleotide, 2'-O-propyl modifications have been incorporated into the 5'- and 3'-ends of the oligonucleotide, with the eight central bases left as phosphorothioate oligodeoxynucleotides. Hybridization analysis demonstrated that these modifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…In Vitro Nuclease Stability-Oligonucleotide resistance to snake venom 3Ј-phosphodiesterase was determined as described previously (11). Briefly, the oligonucleotides were gel purified and 5Ј-end-labeled with high performance liquid chromatography-purified [␥-…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Vitro Nuclease Stability-Oligonucleotide resistance to snake venom 3Ј-phosphodiesterase was determined as described previously (11). Briefly, the oligonucleotides were gel purified and 5Ј-end-labeled with high performance liquid chromatography-purified [␥-…”
Section: Methodsmentioning
confidence: 99%
“…The long half-lives of some PKC proteins (and other proteins which have been targeted with antisense oligonucleotides) have proven problematic, as we have found that the most widely used oligonucleotide modification available, the phosphorothioate (PϭS) oligodeoxynucleotide, is metabolized in cells over time. This leads to a loss of activity over a 48 -72-h period, which can make inhibition of some PKC isozymes difficult (7,8,11).…”
mentioning
confidence: 99%
“…Indeed, the antisense oligonucleotide ISIS 3521, an oligonucleotide of 20-mer that impedes the expression of PKCα, markedly reduced tumor proliferation and invasion in laboratory animals [134,135]. ISIS 3521 is now undergoing clinical testing [136,137].…”
Section: Pkc-inhibiting Agents: Preclinical and Clinical Studiesmentioning
confidence: 99%
“…An alternative approach is the use of ASOs (Dolnik 1991, Crooke 1995. Because the specificity of ASOs is derived from selective hybridization to a target mRNA sequence, it is possible to design oligonucteotide inhibitors of members of a closely related gene family such as PKC (Dean & McKay 1994, McKay et al 1996. ISIS 3521 is a 20-mer phosphorothioate oligodeoxynucleotide (ODN) that hybridizes to the 3 0 -untranslated region of human PKC mRNA, resulting in its degradation by RNase H. Preclinical evidence of antitumor activity and PKC inhibition by an antisense mechanism was demonstrated in a variety of in vitro and in vivo experiments (Dean et al 1994).…”
Section: Protein Kinase C (Pkc) and Isis 3521mentioning
confidence: 99%